Role of Growth Hormones in Unpredictable Reproductive Behaviour of Cedrus deodara - Phular, Karuna; Sharma, Rajesh; Ginwal, H. S. (Indian Forester, 2020)
The diplohalontic life cycle of conifers with Cedrus deodara, as no exception alternates between reproductive phase and vegetative phase and results in good seed year once in every three to four years interval. The uncertainty of reproduction is not predictable and can be attributed to change in the hormonal levels in the trees at the time of reproduction. Auxins and gibberellins play a major role in flowering of day light plants like conifers, hence an attempt to understand the role of growth hormones leading to the unpredictable behaviour of Cedrus deodara was made, for which over 900 trees were marked at three different sites, viz. Cheog forest, HFRI campus in Himanchal Pradesh and Chakrata forest in Uttarakhand and their reproductive behaviour was observed since the time of pollination to cone production. Samples from plants with different reproductive behaviour like, male, female, monoecious and vegetative were collected for extraction and estimation of growth hormones and find out the relationship between the levels of different hormones and cone production, if any.